Hypertrophic Cardiomyopathy and Tricuspid Regurgitation with Right Heart Failure Mimicking Constrictive Pericarditis: A Rare Case Report (University Heart Journal, 2016)
Cardiomyopathy is the measurable deterioration of the function of the myocardium for any reason, usually leading to heart failure. Tricuspid regurgitation may result from structural alterations of any one or all of the components of the tricuspid valve apparatus which include the leaflets, chordae tendinae, annulus, and papillary muscles or adjacent right ventricular muscle. We are reporting a case of Cardiomyopathy with tricuspid regurgitation with right heart failure in a 38 years male. Preoperatively he was diagnosed as a case of constrictive pericarditis. Diagnosis of Tricuspid regurgitation with cardiomegaly was confirmed peroperatively. During operatrion tricuspid valve anatomy dimunited and severe tricuspid regurgitation was identified. Grossly dilated RA, RV identified and other anatomy of heart was normal. De-Vega Tricuspid anuloplasty done with pledgeted stich 2-0 polyster. Part of right atrial wall (2X2.5 inch) excised and resected portion sent for histopathology. Postoperative course was uneventful with marked improvement of symptoms.University Heart Journal Vol. 11, No. 1, January 2015; 45-47